Heritage of the Professor of the Kyiv Theological Academy Vasyliy Ekzempliarskiy as a Prologue to the History of the Domestic “Public Theology” - Volodymyr BUREHA (Богословські роздуми: Східноєвропейський журнал богословʼя)
The article is dedicated to the intellectual history of the early twentieth century of the Kyiv Theological Academy. In the years of the First Russian Revolution (1905-1907) in the Kyiv Theological Academy was formed a liberal party of professors. They were advocating the idea of a reform of theological education system. In particular, the reformers called for the democratization of the inner life of the theological academies, for the academies autonomy in relation to the power of the bishops, and for the election of higher administrative positions in the academies. In addition, liberal professors tried to find new ways of Orthodox theology developing. They advocated the approximation of theology to the needs of the present, for overcoming the closeness and scholasticity of academic theology. One of the brightest representatives of this ideological course was the professor of the Kyiv Theological Academy Vasiliy Ekzemplyarskiy (1875-1933). In teaching moral theology, he tried to discuss with the students the actual social problems.